Magnetic Resonance Imaging Features of Extradural Spinal Neoplasia in 60 Dogs and Seven Cats - Auger, Mylène; Hecht, Silke; Springer, Cary M. (Frontiers in Veterinary Science, 2021)
This retrospective study describes the MRI features of extradural spinal neoplasia in 60 dogs and seven cats to identify potential distinguishing features between tumor classes and individual tumor types within each class. In dogs, mesenchymal tumors were most common (48%), with undifferentiated sarcomas being the predominant tumor type. Round cell neoplasms were second most common (35%), with lymphoma and multiple myeloma/plasma cell tumor comprising the majority of cases. Only two benign tumors were identified. In cats, lymphoma was most common (5/7), with one case of mesenchymal neoplasia and one case of metastatic carcinoma. Despite some overlap, certain imaging features were able to help prioritize differential diagnoses. The combined features that predicted round cell neoplasia (84%) included the preservation of vertebral shape, homogeneous contrast enhancement, and lesion centering on bone. The combined features that predicted mesenchymal neoplasia (73%) included altered vertebral shape, heterogeneous contrast enhancement, and lesion centering on paraspinal soft tissues. Round cell neoplasms were more likely to have cortical sparing, preservation of overall shape, lesion centering on bone, small soft tissue tumor size, and homogeneous contrast enhancement. Both epithelial and mesenchymal neoplasms were more likely to have cortical lysis, a cavitary component to the soft tissue mass and medium to large soft tissue mass size. The findings of this study can aid in prioritizing differential diagnoses in cases of extradural spinal neoplasia in cats and dogs, which can impact case management, but tissue sampling remains the gold standard for definitive diagnosis.